Aṡar al-Yūtyūb Kawasīlah Ta‘līmiyyah Tafā‘uliyyah fī Tanmiyyah Mahārah al-Kalām Ladāi Ṭullāb al-Marḥalah al-Mutawassiṭah - Putri, Syifa Firdausi; Najib, Ahmad Farhan Rif'an; Azizah, Shofa Afifah Nur; Wahyudi, Muhammad (Aphorisme: Journal of Arabic Language, Literature, and Education, 2025)
This study aims to examine YouTube as an interactive educational tool to improve Arabic speaking skills among middle school students. As digital media becomes increasingly integrated into the learning process, YouTube provides audio-visual content that can simulate real-life conversational contexts, making it a relevant learning resource in today’s language teaching. This study uses a quantitative quasi-experimental design. Thirty female second-grade students were purposively selected and evenly divided into an experimental group, which received Arabic-speaking instruction through YouTube videos, and a control group, which was taught using traditional methods. The study's hypothesis states that there is a statistically significant difference in speaking skill improvement between students who use YouTube and those who receive conventional instruction. To test this hypothesis, an independent samples t-test was used. The study lasted six weeks, during which data were collected through pre-tests and post-tests, interviews with teachers, and documentation of teaching materials and student progress. Statistical analysis was carried out using SPSS and revealed a significant improvement in the experimental group’s speaking ability, with a post-test mean of 42.13 and an N-Gain of 0.60 (moderate), compared to the control group’s mean of 26.53 and N-Gain of 0.11 (low), indicating that YouTube was much more effective in improving speaking performance. These results indicate that YouTube impacts Arabic language instruction as a practical and engaging strategy to develop students’ communicative competence. Although the findings are promising, the small sample size and the study’s focus on a single institution call for broader research to verify these results. Therefore, other researchers in the same field are expected to address these limitations.